2011
DOI: 10.1007/s11517-010-0729-4
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 induces the differentiation of bone marrow-derived mesenchymal cells into chondrocytes

Abstract: Injured articular cartilage has a poor capacity for spontaneous healing. So far, a satisfactory solution to repair the injured cartilage has not been found, but transgenic therapy might be a promising treatment. This study aims to evaluate the potential of transfecting bone morphogenetic protein-7 (BMP-7), a secretory protein, into bone marrow-derived mesenchymal stem cells (BMSCs), in inducing the differentiation of bone marrow stromal cells into chondrocytes in vitro. The phenotypes of the cells were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Recent studies have confirmed that BMP-7 is a strong chemotactic component in cartilage cells produced by mesenchymal stem cells, and it can promote cartilage cells to secrete specific extracellular matrix (proteoglycans and collagen type II). And BMP-7 can induce the differentiation of BM-MSCs into cartilage cells, and that it offers a greater efficiency in repairing cartilage and subchondral bone defects (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that BMP-7 is a strong chemotactic component in cartilage cells produced by mesenchymal stem cells, and it can promote cartilage cells to secrete specific extracellular matrix (proteoglycans and collagen type II). And BMP-7 can induce the differentiation of BM-MSCs into cartilage cells, and that it offers a greater efficiency in repairing cartilage and subchondral bone defects (16).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 [78,79,80] TGF-β3 [81,82] CDMP1 [83] IGF-1/BMP-2 [85] IGF-1/FGF-2 [90] BMP-7 [88] Wnt11 [91] So So ZN…”
Section: Cartilage Productionmentioning
confidence: 99%
“…The appropriate chondrogenenic process was appreciated in these so-transformed cells [85], despite the fact that the overexpression [86] and the treatment of BMP-2 alone is reported to facilitate osteogenesis in MSCs [87]. There is an example of the application of another BMP family member, BMP7, in which the BMP7 gene transfection of BM-MSCs resulted in favorable chondrocyte formation [88]. Interestingly, the IGF-1 overexpression was able to stimulate the expression of the Sox9 gene; however, the expression of osteogenic marker genes was also elevated, suggesting that IGF-1 gene transfections into BM-MSCs with chondrogenic purposes should be considered cautiously [89].…”
mentioning
confidence: 99%
“…There is evidence that BMP7 is able to induce the differentiation of bone marrow-derived mesenchymal cells into chondrocytes (19) and might serve as an anabolic activator for chondrocytes in tissue culture (20). In addition, clinical studies have revealed that BMP7 is able to prevent the degeneration of cartilage during inflammatory arthritis (21,22).…”
Section: Introductionmentioning
confidence: 99%